Collective Action and Tragedy of Tank Water. Issue 2 (December 2020) - Sarkar, Sukumar; Ray, Biswajit
Tank irrigation is important in agriculture-dependent developing economies such as India. Since tank water is a common pool resource, managing tanks cost-effectively through collective action (CA) is a challenge. This notion raises the following principal questions on the tank commons: What is the relationship between transaction costs (that is, cost of cooperation) and CA? And what drive the use of tank water for irrigation? For satisfactory answers, we carried out field studies on 127 farmers of seven tank villages in the districts of Bardhaman and West Midnapore in West Bengal, India between September 2015 and May 2017. Interesting findings have emerged from our study. We notice that CAs are inversely correlated with transaction costs in the study sites. Regarding the factors influencing tank water use (WU) we find based on Logit models that CA matters in WU significantly and positively. This impact of CA on WU is also robust irrespective of the model specifications. However, low income households participate more by offering labour than money but unfortunately they seem to have no primary motives for tank reconstruction. Moreover, in communities where tanks are large, local people's participation more in terms of labour and such participation in reconstruction of the tanks is their primary motive, and also where the institutional arrangements are both formal and informal, people tend to use tank water more. The practical implication is that the absence of Water User Association and hence proper collaborative management coupled with weak nestedness between the village people and the State is one of the major causes of inadequate tank WU, leading to the decline of the tank commons. JEL: Q01, Q25